Maintenance management for smart school building / Maizatul Nadiah Mohd Sharif - Mohd Sharif, Maizatul Nadiah (Faculty of Architecture, Planning and Surveying, 2013)
Maintenance management is one of the key components on having the good school building and environment. The primary purpose of having the maintenance management at the school is to maintain the facilities at the school, so staff, teacher and especially student who always use the facilities such as cafeteria, science lab and swimming pool. The school buildings across the nation are aging and becoming a barrier to optimize learning and teaching. The aim of this research is on how to ensure good operation of the maintenance management for the smart school at the Klang Valley. Among objectives of this research are to understand the operation of the maintenance management at smart school building, identify the problem in maintenance management and give the recommendation on how to reduce it at smart school. The research was carried out in three (3) different smart school; R.E.A.L Education Group, Asia Pacific Smart School and SRI KDU International Smart School. Data was collection by having the interview and a set of questionnaire was distributed randomly to the staff and teacher at the school to get their respond. It was found that the maintenance management for every school that been studied is having the same problem in their maintenance management which poor in performance, lack of maintenance and narrow work planning.